Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. Agile Internal Audit from the Perspectives of Saudi Internal Auditors: An Exploratory Study Mr. Anan Abdulaziz Almahyawi, Co-Prof. Fahdah Sultan Alsudairi 2. Violations of concealment of economic activities in the Saudi Legal Dr. Waleed Ali Daghriri 3. The reality of administrative training in Aseer Education Administration and the obstacles to its development from the employees’ point of view Mrs. Mona Ahmed Yahya Al-Marhi, Mrs. Sohair Ahmed Mohammed Al-Ghamdi, Mrs. Nouf Saleh Saeed Bahashwan, Prof. Bader Saleh Al-Abdi 4. The impact of leadership styles on the performance of workers in health organizations, An applied study in Asir Central Hospital during 2021 Mr. Nabil Ali Saeed Alshahrani 5. The relationship between being in places intended for the use of narcotic drugs and psychotropic substances – A descriptive and analytical study – Dr. Hakami, Hafiz Mohammed 6. A reading of the Qatari state’s trends from the Syrian crisis 2011 – 2018 Dr. OUASSFI BEN MUSSA 7. Using (TOPSIS) technique for decision-making in Managerial Accounting: A case study Dr. Ahmad Husain Alyaseer 8. Evaluating Corporate Social Responsibility Reporting Practices in the Sultanate of Oman (2016 to 2018) Mr. Sultan Said Al-Maauli